Information and society/ Ilina Syazwani Musa - Musa, Ilina Syazwani (2012)
The library is closely related to the development of the human civilization. The term 'information society' refers to a society in which creation, dissemination, and use of information is a significant economic, political and cultural activity. Three factors that act as indicators towards information society, which are information, connectivity and social capital. The library plays and important role to cultivate reading culture and lifelong learning environment for the community. The distribution of information has begun from the early of establishment of writing system and now it involved to the new forms of communication, such as computers. However, because of a gap of information accessibility, there exist information rich and information poor among the societies. The person who is information literate will have a better social life than those who are not information literate, in term of income and status in society.